Swedish - Finnish glossary: funeral - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with funeral words. Contains approximately 140 entries. 2009.

Svensk-sverigefinsk ordlista med begravningsord. Innehåller ca 140 ord. 2009.
Svensk-finsk ordlista: begravning
Keywords: funerals; begravningar; Funeral Rites; Begravningsritualer; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur